De l’évolution de l’esclavage à Cuba - Jean-Pierre Tardieu (Caravelle)
For José Agustín Caballero (1762-1835), the main obstacle to the economic development of the island of Cuba is to be found in the conservatism of the big landowners whose attitude towards slavery manifests ineptitude, hence a high dependence on the slave trade’s foreign capital, and, as a result, a great financial fragility. Caballero advocates from 1791 to 1798 a double reform through an adapted education : preparation for the social integration of the servile class by a gradual abolition, of course, but also the modernization of education for the wealthy class, from the primary schools to the higher education.